The Role of the Muslim Woman in Spreading Islamic Knowledge - Shireen Ahmed Mohammed; Kamal Sadiq Yaseen Lak (Islamic Sciences Journal, 2025)
Praise be to Allah, the Lord of all worlds, and peace and blessings be upon our master Muhammad (Peace be upon him) and upon his family and all his companions until the Day of Judgement. As for what follows: Islamic knowledge is regarded as a fundamental pillar in the construction of a society that is dedicated to its beliefs and compliant with its laws. Women have significantly contributed to the propagation of this knowledge through teaching, memorisation, and dissemination.This research focuses on the role of Muslim women in disseminating Islamic jurisprudence. They serve as the essential foundation for building strong, cohesive, and interconnected societies, as well as in the endeavour of calling to Allah Almighty. Islam has honoured women by granting them rights and imposing duties upon them. Women have been entrusted with the vital task of upbringing and preparing righteous generations who will uphold this religion. Undoubtedly, empowering Muslim women with Islamic knowledge contributes to achieving intellectual integration in the nation and reforming the individual and society